2010
DOI: 10.1007/s00442-010-1571-y
|View full text |Cite
|
Sign up to set email alerts
|

A cold-adapted reptile becomes a more effective thermoregulator in a thermally challenging environment

Abstract: Thermoregulation is of great importance for the survival and fitness of ectotherms as physiological functions are optimized within a narrow range of body temperature (T(b)). The precision with which reptiles thermoregulate has been proposed to be related to the thermal quality of their environments. Although a number of studies have looked at the effect of thermal constraints imposed by diel, seasonal and altitudinal variation on thermoregulatory strategies, few have addressed this question in a laboratory set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 45 publications
3
70
0
Order By: Relevance
“…Warm temperatures are necessary for normal physiologic processes such as digestion, growth, reproduction, and immune function (Kanui et al, 1991;Dickinson and Fa, 1997). Most reptiles possess the ability to raise and lower their body temperature in response to environmental fluctuations through behavioral and physiological mechanisms, such as basking, changes in posture, vascular shunting, metabolic heat production (limited to a few species), and changes in heart rate (hysteresis) (Seebacher and Franklin, 2005;Besson and Cree, 2010;Raske et al, 2012;Zhang et al, 2008). Most reptiles possess the ability to raise and lower their body temperature in response to environmental fluctuations through behavioral and physiological mechanisms, such as basking, changes in posture, vascular shunting, metabolic heat production (limited to a few species), and changes in heart rate (hysteresis) (Seebacher and Franklin, 2005;Besson and Cree, 2010;Raske et al, 2012;Zhang et al, 2008).…”
Section: Temperaturementioning
confidence: 99%
“…Warm temperatures are necessary for normal physiologic processes such as digestion, growth, reproduction, and immune function (Kanui et al, 1991;Dickinson and Fa, 1997). Most reptiles possess the ability to raise and lower their body temperature in response to environmental fluctuations through behavioral and physiological mechanisms, such as basking, changes in posture, vascular shunting, metabolic heat production (limited to a few species), and changes in heart rate (hysteresis) (Seebacher and Franklin, 2005;Besson and Cree, 2010;Raske et al, 2012;Zhang et al, 2008). Most reptiles possess the ability to raise and lower their body temperature in response to environmental fluctuations through behavioral and physiological mechanisms, such as basking, changes in posture, vascular shunting, metabolic heat production (limited to a few species), and changes in heart rate (hysteresis) (Seebacher and Franklin, 2005;Besson and Cree, 2010;Raske et al, 2012;Zhang et al, 2008).…”
Section: Temperaturementioning
confidence: 99%
“…Although I did not measure operative temperatures, or soil temperatures throughout the study site, tortoises appeared to be thermoregulators, as confirmed by the relationship between inguinal and soil temperatures at the sites where tortoises were found. Nevertheless, spring inguinal temperatures were higher in a relatively warm year (2002) than in cooler years (2001,2003), as a direct result of the warmer thermal environment, or possibly reflecting variation in thermoregulatory opportunities among years, or plasticity in selected body temperatures (Besson and Cree, 2010;Glanville and Seebacher, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…However, maintaining high body temperatures can also have important consequences (see review in Besson and Cree, 2010;Dubois et al, 2009). Most notably, individuals may need to spend considerable time gaining heat.…”
Section: Homopus Signatus Body Temperatures In Relation To Its Ecologymentioning
confidence: 99%
“…Many reptiles maximize thermal benefits by shuttling among microhabitats or altering position in thermally heterogeneous environments to remain within or closer to T set for more extended periods (Christian and Weavers, 1996; Edwards and Blouin-Demers, 2007; Dubois et al, 2009; Besson and Cree, 2010). Assuming turtles in our study were behaviorally thermoregulating, fire-maintained longleaf forest could offer more opportunities to maintain T b closer to or within T set .…”
Section: Discussionmentioning
confidence: 99%
“…While all of these processes are dependent on temperature in ectotherms (Huey, 1982; Angilletta et al, 2002), perhaps the relatively low variation in thermal characteristics among habitats and overall benign thermal environment of our system minimizes the influence of temperature in habitat use “decisions”. Ectotherms must invest more effort into thermoregulation in extreme climates with low thermal quality, such as at higher latitudes and elevations (Blouin-Demers and Nadeau, 2005); as a result, we typically see stronger thermoregulatory behaviors, such as habitat selection and activity timing, in thermally challenging environments (Blouin-Demers and Weatherhead, 2001; Edwards and Blouin-Demers, 2007; Besson and Cree, 2010). In our study, the largest difference in thermal quality ( d e ) between habitats in any season (for comparable positions) was 1.1, and all habitats were of relatively high thermal quality during most of the active season compared to measures from terrestrial habitats in colder climates (Blouin-Demers and Weatherhead, 2001; Blouin-Demers and Nadeau, 2005; Row and Blouin-Demers, 2006).…”
Section: Discussionmentioning
confidence: 99%